Development of a novel immunocompetent murine tumor model for urothelial carcinoma using in vivo electroporation - Soleder, Stefan; Gengenbacher, Nicolas; Mogler, Carolin; Eckstein, Markus; Runge, Anja; Kriegmair, Maximilian; Augustin, Hellmut (Scientific reports, 2024)
A lack of advanced preclinical mouse tumor models impedes the progress in urothelial carcinoma research. We present here a novel fast, robust, reliable, and highly reproducible model for the genetic induction of bladder cancer in immunocompetent mice. Different sets of oncogenic transposons (Cmyc, Kras) and Cre drivers were transfected into the murine bladder wall of two different genetic backgrounds (Trp53fl/fl and BrafV600E, Ptenfl/fl, Ctnnb1exon3-fl/fl). Transfection was carried out using in vivo electroporation of the bladder after surgical exploration and transmural or transurethral intravesical plasmid injection. Up to 100% of animals developed urothelial carcinomas of the bladder. Time to tumor onset ranged from 16 to 97 days with a median of approximately 23 days in the fastest groups. Histological examination identified orthotopic urothelial carcinomas in most cases, in some experimental groups up to 100%. The resulting tumors were highly invasive and often metastatic. Metastases were found in up to 100% of tumor bearing mice per group. Taken together, this study establishes the proof-of-principle that in vivo electroporation can be versatilely employed as a reliable, fast, and robust method for the highly reproducible induction of urothelial carcinomas in the murine bladder wall. This novel murine tumor model could pave the way towards more easily modelling subtype specific urothelial carcinomas in mice.
Gesehen am 26.03.2025